The Protestant expansion in the Eastern Mediterranean: the presence and the editorial activities of the American Protestant Missionaries Societies in the Greek-speaking geographical space (1808–1856) - Papoulidis, Kiriakos (Balcanica Posnaniensia. Acta et studia, 2011)
The article is devoted to the activities of American Protestant missionary societies in the Greek-speaking regions of the eastern Mediterranean basin between 1808 and 1856. The author analyzes the origins of the Protestant missionary movement and its development in the Balkans and the Middle East. The subject is important for research on the history of Protestant missions, religious and cultural contacts, and the influence of the United States in the Mediterranean region during the nineteenth century. The aim of the article is to present the missionary and publishing activities of American Protestant organizations among Greek-speaking communities. The author employs the historical method and an analysis of sources concerning the activities of missionary societies such as the American Board of Commissioners for Foreign Missions. The study demonstrates that Protestant missionary organizations developed intensive educational and publishing activities, producing religious texts and supporting the development of schooling. The author emphasizes that Protestant missions formed part of the broader process of religious revival associated with the Great Awakening and the idea of evangelizing the East. The results of the analysis indicate that the activities of Protestant missions played an important role in shaping religious and cultural contacts between the Anglo-Saxon world and Greek communities in the eastern Mediterranean basin.